NILAI-NILAI PENDIDIKAN MORAL DALAM NASKAH AL-MALHUDHAT KARYA KH. AHMAD ASRORI AL ISHAQI - Husnul Yaqin; Abdul Muhid (Universitas Islam Lamongan, 2022)
The attitude of faith and piety as the basis of moral education is essential for human existence, especially in the current millennial era. This paper seeks to explore and describe the educational values contained in the al-Malhudhat text by KH. Ahmad Asrori Al-Ishaqi. This research is literature research that uses documents or manuscripts as the primary source. This study succeeded in finding that Kiai Asrori's original idea in the al-Malhudhat text convincingly suppressed the high moral aspect. The text of al-Malhudlat studied in this paper clearly shows the moral values that must be possessed by a learner, such as purity of soul, patience, humility and spiritual values, which are very thick with the nuances of Sufism.